2011
DOI: 10.18632/oncotarget.370
|View full text |Cite
|
Sign up to set email alerts
|

MED12 exon 2 mutations are common in uterine leiomyomas from South African patients

Abstract: Uterine leiomyomas, or fibroids, are extremely common tumors. Regardless of their benign nature, fibroids can cause considerable morbidity. Women with African ancestry have a threefold increased risk of developing uterine leiomyomas with a greater symptom severity when compared to white women. Recently, we demonstrated that exon 2 of the MED12 gene is somatically altered in up to 70 per cent of uterine leiomyomas in a series of Finnish (Caucasian) patients. To validate these results in other populations, we se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
77
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 13 publications
12
77
1
2
Order By: Relevance
“…Further studies must be performed to clarify this matter. In addition, the results of the present study also showed that the MED12 mutation frequency in small hysteromyomas was higher than that in large hysteromyomas, which was consistent with the study by Mäkinen et al (7).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Further studies must be performed to clarify this matter. In addition, the results of the present study also showed that the MED12 mutation frequency in small hysteromyomas was higher than that in large hysteromyomas, which was consistent with the study by Mäkinen et al (7).…”
Section: Discussionsupporting
confidence: 93%
“…The reported mutation frequency in the South African population appeared to be lower than that found in Caucasian individuals, which may be a result of the size of the hysteromyoma in these patients. The tumors of the individuals of the South African population were usually large, and according the study by Mäkinen et al, the size of the hysteromyoma may be negatively correlated with the presence of mutations (7). In the present study, the mutation frequency of MED12 in hysteromyoma was 54.39%, similar to that of the individuals of African descent, and lower than that of the Finnish or North American populations.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…It has been reported that in patients suffering from uterine leiomyoma, MED12 mutations are found in stem cells, which leads to unlimited growth and tumor. The mutation sites in MED12 are located in the second exon (Makinen et al, 2011a(Makinen et al, , 2011bJe et al, 2012;Markowski et al, 2012). It was recently reported that the second exon mutation occurs in 52.2% of uterine fi broid patients while the mutation is not found in other tumors (Je et al, 2012), implicating the involvement of MED12 in the disease.…”
Section: Med12 Mutations and Uterine Leiomyomamentioning
confidence: 99%